1970
DOI: 10.1002/app.1970.070140915
|View full text |Cite
|
Sign up to set email alerts
|

Network formation in poly(ethylene terephthalate) by thermooxidative degradation

Abstract: synopsisGelation of poly(ethy1ene terephthalate) by heating at 263°-3000C was investigated. Under nitrogen flow, crosslinks were scarcely formed. However in air, degradation and crosslinking were common, and these were accelerated by purging gaseous and sublimable degradation products out of the system with a stream of air. The main component of the sublimate was terephthalic acid. Infusible and insoluble gel was treated with methanol at 26OoC, and then the methanolysis products were separated into two parts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
6

Year Published

1979
1979
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 4 publications
1
31
0
6
Order By: Relevance
“…They result in crosslinked products and in the formation of compounds such as aldehydes, carboxylic acids and vinyl esters, as reported in the case of PET. 93,94 On the other hand, the presence of oxygen has little effect on the thermal resistance of wholly aromatic polyesters below 550…”
Section: Thermal and Thermo-oxidative Degradationmentioning
confidence: 99%
“…They result in crosslinked products and in the formation of compounds such as aldehydes, carboxylic acids and vinyl esters, as reported in the case of PET. 93,94 On the other hand, the presence of oxygen has little effect on the thermal resistance of wholly aromatic polyesters below 550…”
Section: Thermal and Thermo-oxidative Degradationmentioning
confidence: 99%
“…Catalysts (commercially available guaranteed grade) and a radical inhibitor, 1,3,4, Shell Fine Chemicals), were used without further prufication.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 3 shows the thermal degradation reactions that are believed to occur during melt processing of PET. 15 Other degradation mechanisms of PET, namely hydrolytic and thermooxidative, are considered to be negligible under the selected experimental conditions. More details about PET degradation are given by Yoda et al 15 In the case of thermal degradation, at first, random scission of PET chain takes place, initiated by chain cleavage forming carboxylic end groups and vinyl esters, aldehydes, and carbon dioxide.…”
Section: Process Stability Of Pet In a Batch Mixermentioning
confidence: 99%
“…15 Other degradation mechanisms of PET, namely hydrolytic and thermooxidative, are considered to be negligible under the selected experimental conditions. More details about PET degradation are given by Yoda et al 15 In the case of thermal degradation, at first, random scission of PET chain takes place, initiated by chain cleavage forming carboxylic end groups and vinyl esters, aldehydes, and carbon dioxide. 15 Yoda further suggested that vinyl esters accumulate to a certain concentration and then react with polyester chains, resulting in extension/branching/crosslinking and acetaldehyde generation.…”
Section: Process Stability Of Pet In a Batch Mixermentioning
confidence: 99%
See 1 more Smart Citation